The Current State of Vascular Surgery Presence in Bilibili Video Platform of China - Wu, Haoliang; Wang, Zhiwei; Li, Mingxing; Sun, Peng; Zhang, Liwei; Zhang, Cong; Wei, Shunbo; Xie, Boao; Lou, Chunyang; Qiao, Zhentao; Liu, Yuanfeng; Bai, Tao; et al. (Frontiers in Surgery, 2022)
Background: With the development of the Internet, more and more patients search for disease-related information on the video platform during the treatment process, and physicians also look for learning materials through the video platform. Bilibili is one of the most popular video platforms in China. This study evaluated information on various interesting topics and related surgical procedures searched through Bilibili. Method: The Bilibili platform was independently queried for 12 common vascular diseases or related surgical procedures between October and November 2021 by two independent authors using Baidu search engine. Information about the video and uploader was collected, and descriptive analyses of the overall and first page results were performed. Results: A total of 3998 search results were retrieved by searching 12 vascular related topics, of which 2225 actual videos (55.7%) were finally confirmed to be related to medicine. Videos for the public accounted for 84.8% in these 2225 videos. In addition, 50.5% of the video results were uploaded by vascular surgeons, 12.4% by other specialties, 17.7% by organizations, and 19.4% by other individuals. The total number of videos searched for varicose vein and peripheral vascular disease were the largest, and the total number of leg amputation was the smallest. The largest number of videos for medical professionals were about pulmonary embolism, and the smallest were about leg amputation. On the first pages, 168 results (70.0%) were actually medically relevant and only 7.7% of the videos were uploaded by vascular surgeons. Conclusion: On the Bilibili platform, videos about vascular diseases are extensive but not comprehensive. The videos uploaded by vascular surgeons are rare and results searched are not precise. The online presence of vascular surgeons needs to be improved, which may partially solve the problem of low-quality video due to lack of strict management and censorship.